Global and regional source attribution of Shiga toxin-producing Escherichia coli infections using analysis of outbreak surveillance data. (2019) - Pires, Sara M.; Majowicz, Shannon; Gill, Alexander; Devleesschauwer, Brecht
Abstract: Shiga toxin-producing Escherichia coli (STEC) infections pose a substantial health and economic burden worldwide. To target interventions to prevent foodborne infections, it is important to determine the types of foods leading to illness. Our objective was to determine the food sources of STEC globally and for the six World Health Organization regions. We used data from STEC outbreaks that have occurred globally to estimate source attribution fractions. We categorised foods according to their ingredients and applied a probabilistic model that used information on implicated foods for source attribution. Data were received from 27 countries covering the period between 1998 and 2017 and three regions: the Americas (AMR), Europe (EUR) and Western-Pacific (WPR). Results showed that the top foods varied across regions. The most important sources in AMR were beef (40%; 95% Uncertainty Interval 39–41%) and produce (35%; 95% UI 34–36%). In EUR, the ranking was similar though with less marked differences between sources (beef 31%; 95% UI 28–34% and produce 30%; 95% UI 27–33%). In contrast, the most common source of STEC in WPR was produce (43%; 95% UI 36–46%), followed by dairy (27%; 95% UI 27–27%). Possible explanations for regional variability include differences in food consumption and preparation, frequency of STEC contamination, the potential of regionally predominant STEC strains to cause severe illness and differences in outbreak investigation and reporting. Despite data gaps, these results provide important information to inform the development of strategies for lowering the global burden of STEC infections.